2012
DOI: 10.5194/aab-55-1-2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fattening performance and slaughter value of local Hungarian cattle breeds to international breeds

Abstract: The objective of the trial is to compare fattening performance, slaughter results and meat quality of bulls from international cattle breeds with local Hungarian breeds fattened under the same conditions. Altogether 62 growing bulls -Angus, Charolais, Holstein, Hungarian Grey, Hungarian Simmental, Charolais × Hungarian Grey -were fattened in small groups. The daily gain varied from 897 (Hungarian Grey) to 1 240 g/day (Angus). In general, the lower gain value is caused by the semi-intensive fattening system wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
4
16
4
Order By: Relevance
“…Carcass dressing percentage was highest in group AA (56.8%), followed by group AK (55.3%) and group WK (54.1%). Similar dressing percentage values of Angus bulls were reported by (Holló et al, 2012) who also noted the highest carcass fat content in the Angus breed. In our study, the lowest content of internal fat was noted in the carcasses of WK bulls (2.8%, Table 5).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Carcass dressing percentage was highest in group AA (56.8%), followed by group AK (55.3%) and group WK (54.1%). Similar dressing percentage values of Angus bulls were reported by (Holló et al, 2012) who also noted the highest carcass fat content in the Angus breed. In our study, the lowest content of internal fat was noted in the carcasses of WK bulls (2.8%, Table 5).…”
Section: Resultssupporting
confidence: 85%
“…5.5) in all groups. Holló et al (2012), compared the fattening performances of 62 bulls of different breeds, including Angus, under identical management conditions. They found that in the semi-intensive fattening system, Angus bulls achieved daily gains above 1200 g when the content of concentrates in the ration was increased.…”
Section: ±08 Explanatory Notes As Inmentioning
confidence: 99%
“…FRISULLO and co-workers (2010), who used X-ray microcomputed tomography to quantify the intramuscular fat content of beef, have found high correlation coeffi cient (r) of 0.9 between percentage object volume and IMF content. Similarly to the current experiment, the intramuscular fat levels measured by CT were generally lower compared to values of the chemical percentage method, but the correlation between mentioned methods was signifi cant (HOLLÓ et al 2012). ANTON and coworkers (2013) compared chemical analysis or dissection with CT in order to determine the intramuscular fat and carcass fat content of beef.…”
Section: Resultssupporting
confidence: 51%
“…In agreement with this, the higher fat content in longissimus muscle resulted in lower Hounsfi eld unit measured average CT value, and with the incensement of CT fat content CT muscle percentage decreased. The CT value of intermuscular and subcutaneous fat contents are associated with negative Hounsfi eld values (-200 --20: HOLLÓ et al, 2007), but for the evaluation for intramuscular fat, positive Hounsfi eld values (-200 -+19: HOLLÓ et al, 2012, +10 -+20: FONT-I-FURNOLS et al, 2014 should also be included in the analysis. The average CT fat content of longissimus was lower (~1%) than chemical fat content similarly to previous fi ndings of ANTON et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…So far in Latvia there have been separate studies of beef cattle fattening, however, there is a lack of research on the most appropriate choice of breeds of young animals for fattening with grass forage. Many foreign scientists (Hollo et al, 2012;Jukna et al, 2017;Pesonen, Honkavaar, & Huuskonen, 2013) have researched the growth of beef cattle breeds, fattening and carcass quality characteristics, but in general, these studies have been conducted on the intensive fattening conditions. The aim of this study was to explain the fattening results of HE and AB pure-bred bulls and their crosses (from father side HE and AB sires) using grass forage.…”
Section: Introductionmentioning
confidence: 99%